1993
DOI: 10.1073/pnas.90.11.4961
|View full text |Cite
|
Sign up to set email alerts
|

p53 gene mutations and protein accumulation in human ovarian cancer.

Abstract: Mutations of the p53 gene on chromosome 17p are a common genetic change in the malignant progression of many cancers. We have analyzed 38 malignant tumors of ovarian or peritoneal mullerian type for evidence of p53 variations at either the DNA or protein levels. Genetic studies were based on single-strand conformation polymorphism analysis and DNA sequencing ofexons 2 through 11 of the p53 gene; mutations were detected in 79% of the tumors. These data show a statistically significant association between mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
146
0
6

Year Published

1996
1996
2003
2003

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 267 publications
(160 citation statements)
references
References 31 publications
8
146
0
6
Order By: Relevance
“…In contrast to previous findings (Kern et al, 1989), when tumours were classified according to their histological stage, a multivariate Cox model analysis showed that p53 mutation, rather than 17p allelic losses, was the only independent prognostic factor (Hamelin et al, 1994). Immunohistochemistry (IHC) studies have indicated that mutated p53 is overexpressed in premalignant head and neck lesions (Shin et al, 1994), oesophageal squamous cell carcinomas (Wagata et al, 1993), ovarian cancer (Kupryjanczyk et al, 1993), breast cancer (Faille et al, 1994) and hepatocellular carcinoma (Wolkmann et al, 1994). In colorectal cancer, overexpression of p53 protein has been correlated with poor short-term prognosis (Yamaguchi et al, 1992; p53 mRNA overexpression in colorectal cancer 529 1 00C 1OC 10 100'…”
mentioning
confidence: 68%
“…In contrast to previous findings (Kern et al, 1989), when tumours were classified according to their histological stage, a multivariate Cox model analysis showed that p53 mutation, rather than 17p allelic losses, was the only independent prognostic factor (Hamelin et al, 1994). Immunohistochemistry (IHC) studies have indicated that mutated p53 is overexpressed in premalignant head and neck lesions (Shin et al, 1994), oesophageal squamous cell carcinomas (Wagata et al, 1993), ovarian cancer (Kupryjanczyk et al, 1993), breast cancer (Faille et al, 1994) and hepatocellular carcinoma (Wolkmann et al, 1994). In colorectal cancer, overexpression of p53 protein has been correlated with poor short-term prognosis (Yamaguchi et al, 1992; p53 mRNA overexpression in colorectal cancer 529 1 00C 1OC 10 100'…”
mentioning
confidence: 68%
“…in ovarian carcinomas (Kupryjańczyk et al, 1993;Casey et al, 1996;DiCioccio et al, 1998;Wen et al, 1999), studies on TP53 status and tumour response to cisplatin-based chemotherapy have not so far given equivocal results (Righetti et al, 1996;de Feudis et al, 1997;Baekelandt et al, 1999;Eisenhauer et al, 1999;Fallows et al, 2001;Reles et al, 2001).…”
mentioning
confidence: 99%
“…These genes include the TP53 tumor suppressor at 17p13 (Marks et al, 1991;Okamoto et al, 1991;Tsao et al, 1991;Eccles et al, 1992;Milner et al, 1993), the HER2/neu oncogene at 17q12 (Slamon et al, 1989), the BRCA1 breast-ovarian cancer susceptibility gene at 17q12 (Miki et al, 1994;Merajver et al, 1995), and the NME1 tumor metastasis marker on 17q21-23 (Viel et al, 1995;Scambia et al, 1996;Schneider et al, 1996). Somatic mutations and increased expression of TP53 have been more often reported in high grade and later stage tumors (Berchuck et al, 1994;Kupryjanczyk et al, 1993). Increased expression of HER2/neu accompanied with or without gene ampli®cation is also a feature of some tumors of high grade and late stage (Slamon et al, 1989).…”
mentioning
confidence: 99%